Pengetahuan dan Sikap Keluarga dalam Pencegahan Kekambuhan Rematik - Suryanda Suryanda; Asmawi Nazori; Zanzibar Zanzibar (Poltekkes Kemenkes Pontianak, 2019)
Abstract: Knowledge and Family Attitude in Prevention of Rematical Devices. Rheumatism belongs to a group of rheumatic diseases showing a painful and stiﬀ condition that attacks the limbs or the musculoskeletal system, ie joints, muscles, bones, and tissues around the joint. This study aims to determine the characteristics of family, knowledge and family attitudes in prevention of rheumatic recurrence in Prabumulih 2017. Descriptive analytics with cross-sectional method with Purposive sampling involving all families of rheumatic patients who visited visited Sukajadi Public Health Center East Prabumulih District October to December 2017, amounting 92 person. Sample as many as 87 respondents. Data obtained through questionnaire in the form of checklist and study documentation. Most of the female respondents, high school educated, have the highest average income of Rp 2,000,000 - Rp.3,000,000, self-employment, age of respondent most between 21 years to 30 years.71.1% rheumatic family members rarely relapse, the rest only 29 , 9% often relapse. Knowledge of respondents less 58,6%, 41,3% good. Response respondents 56.3% support eﬀorts to prevent rheumatic recurrence and 43.7% less supportive. The results of chi-square analysis showed a signifcant relationship between family knowledge with rheumatic recurrence in elderly and family attitude with rheumatic recurrence in elderly.Abstrak: Pengetahuan dan Sikap Keluarga dalam Pencegahan Kekambuhan Rematik. Rematik termasuk dalam kelompok penyakit reumatologi yang menunjukkan suatu kondisi nyeri dan kaku yang menyerang anggota gerak atau system musculoskeletal, yaitu sendi, otot, tulang, maupun jaringan disekitar sendi. Penelitian ini bertujuan untuk mengetahui karakteristik keluarga, pengetahuan dan sikap keluarga dalam pencegahan kekambuhan rematik di Prabumulih tahun 2017. Deskriptif analitik dengan metode cross-sectional dengan Purposive sampling melibatkan seluruh keluarga penderita rematik yang tercatat berkunjungke Puskesmas Sukajadi Kecamatan Prabumulih Timur bulan Oktober hingga Desember 2017, berjumlah 92 orang. Sampel sebanyak 87 responden. Data diperoleh melalui kuisioner berupa ceklist dan studi dokumentasi. Sebagian besar responden wanita, berpendidikan SMA, berpenghasilan rata-rata tertinggi Rp 2.000.000 – Rp.3.000.000,pekerjaan wiraswasta, usia responden terbanyak antara 21 tahun hingga 30 tahun.71,1% rematik anggota keluarganya jarang kambuh, sisanya hanya 29,9% sering kambuh. Pengetahuan responden kurang 58,6%, 41,3 % baik. Sikap responden 56,3% mendukung upaya pencegahan kekambuhan rematik dan 43,7% kurang mendukung. Hasil uji analisis chi-square menunjukkan adanya hubungan signifkan antara pengetahuan keluarga dengan kekambuhan rematik pada lansia dan sikap keluarga dengan kekambuhan rematik pada lansia.